Key Attributes for Evaluating the Visitor's Satisfaction at Shopnopuri Artificial Amusement Park of Dinajpur - Huq, Sheikh Majedul; Aktar, Mst. Shuly; Neogy, Taposh Kumar (ABC Journal of Advanced Research, 2022)
This research aims to identify influential factors of visitors' satisfaction in Shopnopuri as a tourism destination and explores the level of satisfaction. A thorough and well-structured questionnaire based on the seven Point Likert scale was developed for primary data collection. A straightforward random sample process was used to choose 295 participants in total for the study. A multivariate analytic method like "Factor Analysis" was utilized to pinpoint the variables. Scale reliability was determined using Cronbach's alpha. The investigation shows that the constructs are very stable and internally consistent. Most observed variables had Cronbach's alpha values between 0.6 and 0.7. The study also demonstrates the substantial correlation between kids' entertainment and satisfaction. On the other hand, the quantity of rides strongly inversely correlates with enjoyment. According to the result of the study, aspects like more expansive Space and variety of foods, cleanliness and security, entertainment, and visitors are all crucial when deciding whether or not to visit Shopnopuri Park. Finally, 39 factors influence visitor satisfaction. First, the outcomes would improve Shopnopuri park's performance and tourist services, leading to increased satisfaction for both domestic and foreign visitors. The study is based on random sampling, so the result cannot be generalized.